Projection of Predatory Pricing Dispute Resolution in The Context of Business Competition Between UMKM in The Digital Economy Era Based on Win-Win Solution - Melki T. Tunggati (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
Predatory pricing disputes between UMKM have been in the public spotlight since the alleged practice of predatory pricing by UMKM businesses selling through the Tik-Tok Shop application. UMKM players in the Jakarta Tanah Abang Market suffered losses due to lack of visitors because the products sold through the Tik-Tok Shop application were twice as cheap. Government policy by modifying the Regulation of the Minister of Trade as a responsive effort in anticipating Predatory Pricing disputes, instead causing losses to Tik-Tok Shop UMKM actors. This research aims to analyze the regulation of Predatory Pricing dispute settlement on business competition practices among UMKM, as well as to offer ideas on the projection of Predatory Pricing dispute settlement on business competition practices among UMKM based on win-win solution. This is a normative research, with statutory, conceptual and comparative law approaches, and analyzed perscriptively. The results of this research show that, First, the Law on Business Competition and Anti-Monopoly, the Law on UMKM, the Law on Trade and the Regulation of the Minister of Trade on PMSE have not regulated the dispute settlement of Predatory Pricing practices in the context of Business Competition between UMKM. Second, the projection of Predatory Pricing dispute settlement in business competition among UMKM must be done by optimizing out-of-court settlements, involving the role of UMKM organizations in Indonesia, assessing with the Rule of Reason approach, and containing business competition dispute settlement norms in the UMKM Law.